2005
DOI: 10.1891/0886-6708.20.6.603
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary People and “Death Work”: Palestinian Suicide Bombers as Victimizers and Victims

Abstract: Applying criminological/victimological concepts and theories, the study addresses the social processes involved in Palestinians' suicide terrorism and describes Palestinians' pathways to suicide bombing. The data are derived from in-depth interviews of 7 male and female Palestinians serving prison sentences in Israel for attempted suicide bombing. The social background, context, and experiences of the interviewees, including their recruitment, interactions with the organizations that produce suicide bombing, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…For instance, Maoz and Eidelson (2007) found in a representative Israeli sample that victim beliefs regarding concerns over Israeli safety and vulnerability predicted the endorsement of policies in support of annexing land from the Palestinians and transferring the population to neighboring Arab countries. Conversely, victim beliefs on the Palestinian side revealed that the motivation for suicide bombing missions is partially influenced by the bombers’ deep sense of victimization, lack of effective nonviolent alternatives, and feelings of oppression and humiliation (Berko & Erez, 2005; Hafez, 2006; see also Bar-Tal & Antebi, 1992; Bar-Tal et al, 2009; Vollhardt, 2009; but see also Ginges & Atran, 2008 for “inertia” effects following humiliation). Whereas this research examined the effects of victim beliefs in general (i.e., not necessarily in competitive contexts), other research has directly examined the relationship between CV and forgiveness (Noor, Brown, Gonzalez, et al, 2008; Noor, Brown, & Prentice, 2008a, 2008b):…”
Section: The Relationship Between Inter-group CV and Inter-group Forgmentioning
confidence: 99%
“…For instance, Maoz and Eidelson (2007) found in a representative Israeli sample that victim beliefs regarding concerns over Israeli safety and vulnerability predicted the endorsement of policies in support of annexing land from the Palestinians and transferring the population to neighboring Arab countries. Conversely, victim beliefs on the Palestinian side revealed that the motivation for suicide bombing missions is partially influenced by the bombers’ deep sense of victimization, lack of effective nonviolent alternatives, and feelings of oppression and humiliation (Berko & Erez, 2005; Hafez, 2006; see also Bar-Tal & Antebi, 1992; Bar-Tal et al, 2009; Vollhardt, 2009; but see also Ginges & Atran, 2008 for “inertia” effects following humiliation). Whereas this research examined the effects of victim beliefs in general (i.e., not necessarily in competitive contexts), other research has directly examined the relationship between CV and forgiveness (Noor, Brown, Gonzalez, et al, 2008; Noor, Brown, & Prentice, 2008a, 2008b):…”
Section: The Relationship Between Inter-group CV and Inter-group Forgmentioning
confidence: 99%
“…Reported experiences of fear ( Habib et al, 2015 ) have been described for people of different personalities and professions in various circumstances and situations, from children playing ( Sandseter, 2009 ) to military activities ( Fenz and Epstein, 1967 ; Caputo, 1977 ; Wallenius et al, 2004 ; Berko and Erez, 2005 ; Cohn et al, 2010 ; Taverniers et al, 2011 ; Bouchard et al, 2012 ; Lane et al, 2012 ; Johnson et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Children, however, may engage in terrorism for other reasons, including thrill and excitement (Berko & Erez, 2007; Katz, 1988; Venhaus, 2010), or the material advantages and economic support that terrorist organizations offer. For adolescent males, interactions with adults and participation in adult activities also provide ways to enhance their status, sense of self-worth, and manliness (Berko & Erez, 2005; Crenshaw, 1986).…”
Section: Palestinian Children In Terrorism: a Reviewmentioning
confidence: 99%
“…The social ecology of Palestinian society suggests a convergence of multi-level risk factors 13 leading to grievances, both collective and personal: individual vulnerabilities, familial hardships, economic necessity, peer group pressures or rewards, a pervasive nationalistic ideology, and an enabling environment (Atran, 2010; Berko & Erez, 2005; Horgan, 2008; McCauley & Moskalenko, 2008; Moghaddam, 2005; Post, 2009; Stern, 2003, 2010). As individual, familial, communal, and societal influences coalesce, children who grow up in conflict zones, where violence is normalized (Masten & Narayan, 2012), are likely to join the fight for a unifying cause, or mobilize it to address various grievances.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation